Gambaran Komplikasi Transurethral Resection of the Prostate pada Pasien Benign Prostatic Hyperplasia - Zuhirman Zuhirman; Desby Juananda; Putry Lestari (Fakultas Kedokteran Universitas Riau, 2016)
Benign prostatic hyperplasia (BPH) is a benign tumor that most common, a serious problem and may affect thequality of life. Transurethral resection of the prostate (TURP) is the gold standard for BPH management. The aim ofthis study was to describe the complications of TURP in patients with BPH. This was a descriptive study by reviewingthe medical records of BPH patients underwent TURPs at RSUD Arifin Achmad, Riau Province in 2011-2015. Therewere 280 medical records fulfilled the inclusion criteria in which showed 93 patients who experienced complicationsof TURP. The most age range was 60-69 years old (12,9%), the mean of the resection duration was 30(10-80) minutesand the mean of weight of the resected prostatic tissue was 30 (10-50)grams. The most common complications wasbleeding (42,9%), urinary retention (27,6%).In the research, we conclude the complications were higher than theones in the literatures.